EFFECTS OF SCARIFICATION ON EMERGENCE AND GROWTH OF DATE PALM (Phoenix dactylifera) IN MAKURDI, SOUTHERN GUINEA SAVANNAH (FUDMA JOURNAL OF SCIENCES, 2022)
The Study was conducted at the nursery of the Teaching and Research Farm Joseph Sarwun Taker University (JOSTUM), Makurdi, Nigeria. The objectives of the study were to evaluate the effect of different seed treatment on seed germination and seedling establishment of some date varieties. Factorial combination of five seed treatments (hot water, cold water, H2ÂSO4, moist sawdust and control) and three varieties (Ajwah, Matinal, and Deglenurr) were laid in a Complete Randomized Block Design replicated three times. Data were collected on Germination Percentage, plant height, leaf width, stem girth and number of leaves at 4 â€“ 18 weeks after planting. Data were subjected to two way analysis of variance (ANOVA) and means separation by Duncan Multiple Range Test (DMRT) at 5% level of significance. Results revealed that sawdust scarification had the highest average germination percentage of 83.20%, plant height (43.91 cm), leaf width (1.96 mm), leaf length (25.17 cm), stem diameter (14.12 mm) and number of leaves (4.50). The results further showed that Degletnur variety had the highest germination percentage of 81.04%, plant height of 25.38cm, stem diameter (7.74 mm) and number of leaf (3.83) at the end of the study. The study revealed that breaking dormancy with sawdust material is effective and Degletnur variety of date palm gave the highest growth parameter so also 2021 season gave the highest in all the parameters considered. Therefore scarification using sawdust should be adopted in breaking dormancy in dateâ€™s palm with Degletnur variety
Keywords: Date palm, Scarification, Varieties and Growth